Pengaruh Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian Produk Ms Glow Dengan Kepercayaan Sebagai Variabel Intervening - Rusmewahni, Rusmewahni; Juni, Sri; Sinaga, Riduan (Economic Development Progress, 2023)
Since 2015, MS Glow Aesthetic Clinic has been present, which currently has 13 branches in big cities in Indonesia (Malang, Surabaya, Bali, Jakarta, Bandung, Sidoarjo, Bekasi, Makassar, Semarang, Medan Bogor and Depok). Now MS Glow has developed into skincare, body care and personal care which has official Distributors, Agents, Members & Resellers throughout Indonesia, and has even penetrated overseas. Established for 8 years since 2013 until now, MS GLOW's internal data has recorded 59. 604 people have joined as MS GLOW sellers spread across 7 countries, namely Indonesia, Malaysia, Japan, Arabia, Hong Kong, Taiwan and Singapore